Pengaruh Pemberian Tugas Mandiri terhadap Hasil Belajar Mahasiswa pada Mata Kuliah Histologi - Serena, Nelda Anasthasia; Masitah, Masitah; Kurniawati, Zenia Lutfi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to determine the effect of giving independent assignments on student learning outcomes in the Histology course. The method used was a quasi-experimental design with a pretest-posttest control group design. The study subjects consisted of two classes: a treatment class given independent assignments and a control class without similar treatment. Data were collected through pretests and posttests, then analyzed using paired t-tests and homogeneity of variance tests. The results showed a significant difference between pretest and posttest scores in the treatment class (p = 0.000 < 0.05), while the control class showed no significant difference (p = 0.348 > 0.05). These findings indicate that giving independent assignments can significantly improve student learning outcomes. Thus, independent assignments are effectively implemented as a learning strategy in the Histology course to train students' independence, responsibility, and critical thinking skills.